Analisis Perbandingan Tingkat Kepuasan Karyawan PT. Harap Panjang Terhadap Layanan Aplikasi ABSS Dengan MYOB Menggunakan Metode Servqual - Nanny Raras Setyoningrum; Fitri Fitri (LPPM Sekolah Tinggi Teknologi Indonesia Tanjung Pinang, 2023)
PT. Harapan Panjang is a company engaged in construction services which is located at Jalan MT. Haryono No. 28 Tanjungpinang. This study relates to the level of user satisfaction of the ABSS application and the MYOB application to PT. Please Long. Data were collected by distributing questionnaires to 34 employees of PT. Please Long which consists of two forms of questionnaire. The purpose of this research is to determine the percentage level of user satisfaction of the application as measured by the Servqual method approach to find out which application is more effective in helping PT. Please Long in recording company finances. The results of this study indicate that the results of the analysis of the satisfaction level of users of the ABSS application have obtained the level of satisfaction felt by users based on the dimensions of Reliability 89.55%, Responsiveness 81.68%, Assurance 87.76%, Empathy 86.36% and Tangibles 80.94 %. Meanwhile, the level of user satisfaction of the MYOB application has obtained the level of satisfaction felt by users based on the dimensions of Reliability 70.07%, Responsiveness 78.42%, Assurance 86.08%, Empathy 84.27% and Tangibles 85.82%. The conclusion of this study is that the percentage of user satisfaction with the ABSS application is higher than the MYOB application.